2012
DOI: 10.1016/j.jpsychires.2012.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for stimulus-general impairments on auditory stream segregation tasks in schizophrenia

Abstract: Background Auditory impairments in schizophrenia have been demonstrated previously, especially for tasks requiring precise encoding of frequency, although it is unclear the extent to which they have difficulty using pitch information and other cues to segregate sounds. We determined the extent to which those with schizophrenia have difficulty using pitch information and other auditory cues to segregate sounds that are presented sequentially. Methods Ten participants with schizophrenia and nine healthy/normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…However, education and IQ significantly predicted mistuned harmonic perception, while only IQ significantly predicted QuickSIN loss. The current findings and previous findings of deficits in sound segregation (Ramage et al, 2012; Weintraub et al, 2012; Wu et al, 2012) are important especially because they suggest that people with SZ have difficulty understanding complex auditory scenes, typical of many urban and social settings that are common in modern human life. It is even possible that difficulties segregating sounds contribute to or exacerbate social withdrawal, anhedonia, and other socially-relevant symptoms in SZ because a general inability to process complex auditory scenes could make it frustrating to participate effectively in noisy social gatherings.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…However, education and IQ significantly predicted mistuned harmonic perception, while only IQ significantly predicted QuickSIN loss. The current findings and previous findings of deficits in sound segregation (Ramage et al, 2012; Weintraub et al, 2012; Wu et al, 2012) are important especially because they suggest that people with SZ have difficulty understanding complex auditory scenes, typical of many urban and social settings that are common in modern human life. It is even possible that difficulties segregating sounds contribute to or exacerbate social withdrawal, anhedonia, and other socially-relevant symptoms in SZ because a general inability to process complex auditory scenes could make it frustrating to participate effectively in noisy social gatherings.…”
Section: Discussionsupporting
confidence: 54%
“…In the laboratory, auditory scene analysis tasks are usually designed to assess the ability to segregate two discrete sounds played concurrently (Alain, 2007) or two series of sounds that are interleaved with each other to form sequential streams of sounds (Snyder and Alain, 2007). Recently, we showed that people with schizophrenia (SZ) had difficulty using frequency, spatial, and amplitude cues to segregate sequential streams (Ramage et al, 2012; Weintraub et al, 2012), and that their event-related brain potentials (ERPs) from auditory cortex were less different in amplitude when the frequency difference between streams was more different, compared to controls (also see Rojas et al, 2007;Weintraub et al, 2012). However, perceptual segregation of concurrent sounds has not been studied in SZ to our knowledge, with the exception of one recent study on speech masking (Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While these correlations are exploratory and require further investigation, they were not significantly correlated with early MMN or simple MMN, suggesting that there is something specific about the late MMN that is reflecting a certain subset of behavioral symptoms. Sz also show other impairments in auditory processing such as the ability to segregate auditory information (Ramage et al, 2012; Weintraub et al, 2012), and in ERP measures of auditory grouping (Coffman et al, 2016), which may be related to the deficits in deviance detection.…”
Section: Discussionmentioning
confidence: 99%
“…Also, schizophrenia patients are slower to learn visual sequences in a serial reaction time task (Adini et al, 2015). Behavioral and electrophysiological evidence suggests impairment in the ability to perceptually segregate auditory streams in schizophrenia (Weintraub et al, 2012; Ramage et al, 2012); however, effects of schizophrenia on electrophysiological indices of segmentation of acoustic patterns into auditory objects has not been studied. In this paper, we identify the electrophysiological correlates of acoustic segmentation in healthy subjects and identify deficits in these measures in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%